2020
DOI: 10.1111/pce.13975
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis to capture the role of heat‐accumulated proteins in moss plant acquired thermotolerance

Abstract: At dawn of a scorching summer day, land plants must anticipate upcoming extreme midday temperatures by timely establishing molecular defences that can keep heat‐labile membranes and proteins functional. A gradual morning pre‐exposure to increasing sub‐damaging temperatures induces heat‐shock proteins (HSPs) that are central to the onset of plant acquired thermotolerance (AT). To gain knowledge on the mechanisms of AT in the model land plant Physcomitrium patens, we used label‐free LC–MS/MS proteomics to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 122 publications
4
34
0
Order By: Relevance
“…Acquired thermotolerance (AT) refers to the plant adaptive capacity to survive noxious HS when exposed to sublethal temperatures, requiring the accumulation of HSPs. Under HS, both transcriptome and proteome-based studies have indicated regulatory responses of HSPs ( Qin et al, 2008 ; Finka et al, 2011 ; Mangelsen et al, 2011 ; Xin et al, 2016 ; Guihur et al, 2020 ; Zhao et al, 2021 ). A conserved subfamily called “heat-induced molecular chaperones” contains the HSP100s, HSP90s, HSP70s, HSP60s, HSP40s, and HSP20s ( Al-Whaibi, 2011 ; Jee, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquired thermotolerance (AT) refers to the plant adaptive capacity to survive noxious HS when exposed to sublethal temperatures, requiring the accumulation of HSPs. Under HS, both transcriptome and proteome-based studies have indicated regulatory responses of HSPs ( Qin et al, 2008 ; Finka et al, 2011 ; Mangelsen et al, 2011 ; Xin et al, 2016 ; Guihur et al, 2020 ; Zhao et al, 2021 ). A conserved subfamily called “heat-induced molecular chaperones” contains the HSP100s, HSP90s, HSP70s, HSP60s, HSP40s, and HSP20s ( Al-Whaibi, 2011 ; Jee, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A conserved subfamily called “heat-induced molecular chaperones” contains the HSP100s, HSP90s, HSP70s, HSP60s, HSP40s, and HSP20s ( Al-Whaibi, 2011 ; Jee, 2016 ). They are 20 times more likely to be heat-induced compared to non-chaperone proteins ( Wang et al, 2004 ; Finka et al, 2011 , 2015 ; Guihur et al, 2020 ). HSP chaperones prevent and repair protein misfolding and aggregation, reducing cell damage ( Ben-Zvi and Goloubinoff, 2001 ; Wang et al, 2004 ; Zeng et al, 2004 ; Liberek et al, 2008 ; Mogk and Bukau, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As plants moved onto land they were subjected to greater heat stress and temperature variability. Guihur, Fauvet, Finka, Quadroni, and Goloubinoff (2021) found that a number of heat‐related mechanisms, such as acquired thermotolerance and accumulation of heat shock proteins are present in the moss Physcomitrium patens . Even the liverwort Marchantia polymorpha has a significant number of genes recognized as related to heat tolerance in angiosperms (Marchetti et al, 2021).…”
Section: Heat Stress Effects On Non‐vascular Plantsmentioning
confidence: 99%
“…Quantitative proteomic studies offer absolute quantification of most of proteome of a cell and offer insights into chaperone mechanisms in proteostasis, in bacteria (Calloni et al, 2012), plant (Guihur et al, 2020), and mammalian cells (Geiger et al, 2012;Gat-Yablonski et al, 2016). Here, we addressed by label-free quantitative proteomic analysis of total and insoluble protein fractions from WT, dnaKJ ( KJ), htpG ( G), and dnaKJ htpG ( KJG) E. coli strains, the physiological role of HtpG and its collaboration with DnaK and the DnaJ cochaperone, in unstressed E. coli cells grown at 30 • C. Confirming earlier findings (Calloni et al, 2012), we observed that in the double KJ mutant, few polypeptides were mildly, albeit significantly less soluble than in WT, but that mass-wise, an important population of DnaK and DnaJ substrates, including many metabolic and respiratory enzymes, was largely reduced, likely by proteases.…”
Section: Introductionmentioning
confidence: 99%